SISTEM DATA LOGGER TINGGI MUKA AIR PADA DAERAH ALIRAN SUNGAI (DAS) BERBASIS MIKROKONTROLER - Muhammad Andang Novinato (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
This paper discusses about a distance of water level measurement system which takes a case in a drainage basin. The collected data in data logger will be used as a reference for decision makes concerning the water rate of flow accumulation so we will be able to predict flood or landslide disaster early. The research purpose was designed a digital water level telemetry system to acquire a database system digitally. The results show that the system works well as expected.